Polyester biodegradability: importance and potential for optimisation - Wang, Yue; van Putten, Robert-Jan; Tietema, Albert; Parsons, John R; Gruter, Gert-Jan M (Green chemistry : an international journal and green chemistry resource : GC, 2024)
To reduce global CO emissions in line with EU targets, it is essential that we replace fossil-derived plastics with renewable alternatives. This provides an opportunity to develop novel plastics with improved design features, such as better reusability, recyclability, and environmental biodegradability. Although recycling and reuse of plastics is favoured, this relies heavily on the infrastructure of waste management, which is not consistently advanced on a worldwide scale. Furthermore, today's bulk polyolefin plastics are inherently unsuitable for closed-loop recycling, but the introduction of plastics with enhanced biodegradability could help to combat issues with plastic accumulation, especially for packaging applications. It is also important to recognise that plastics enter the environment through littering, even where the best waste-collection infrastructure is in place. This causes endless environmental accumulation when the plastics are non-(bio)degradable. Biodegradability depends heavily on circumstances; some biodegradable polymers degrade rapidly under tropical conditions in soil, but they may not also degrade at the bottom of the sea. Biodegradable polyesters are theoretically recyclable, and even if mechanical recycling is difficult, they can be broken down to their monomers by hydrolysis for subsequent purification and re-polymerisation. Additionally, both the physical properties and the biodegradability of polyesters are tuneable by varying their building blocks. The relationship between the (chemical) structures/compositions (aromatic, branched, linear, polar/apolar monomers; monomer chain length) and biodegradation/hydrolysis of polyesters is discussed here in the context of the design of biodegradable polyesters.